Application of bio-organic fertilizer can control Fusarium wilt of cucumber plants by regulating microbial community of rhizosphere soil - Qiu, Meihua; Zhang, Ruifu; Xue, Chao; Zhang, Shusheng; Li, Shuqing; Zhang, Nan; Shen, Qirong (Biology and fertility of soils, 2012)
Fusarium wilt, caused by Fusarium oxysporum f. sp. cucumerinum J. H. Owen, results in considerable yield losses for cucumber plants. A bio-organic fertilizer (BIO), which was a combination of manure composts with antagonistic microorganisms, and an organic fertilizer (OF) were evaluated for their efficiencies in controlling Fusarium wilt. Application of the BIO suppressed the disease incidence by 83% and reduced yield losses threefold compared with the application of OF. Analysis of microbial communities in rhizosphere soils by high-throughput pyrosequencing showed that more complex community structures were present in BIO than in OF treated soils. The dominant taxonomic phyla found in both samples were Proteobacteria, Firmicutes, Actinobacteria and Acidobacteria among bacteria and Ascomycota among fungi. Abundance of beneficial bacteria or fungi, such as Trichoderma , Hypoxylon , Tritirachium , Paenibacillus , Bacillus , Haliangium and Streptomyces , increased compared to the OF treatment, whereas the soil-borne pathogen, Fusarium , was markedly decreased. Overall, the results of this study demonstrate that the application of the BIO was a useful and effective approach to suppress Fusarium wilt and that the high-throughput 454 pyrosequencing was a suitable method for the characterization of microbial communities of rhizosphere soil of cucumber.